Diversification of Mexican Spanish. A Tridimensional Study in New World Sociolinguistics - Hidalgo, Margarita (Contributions to the Sociology of Language [CSL], 2016)
This book covers the analysis of Spanish written from the early 16th to the early 19th century, immediately before the Independent period in most Spanish-speaking colonies. It is based on manuscripts such as the Segunda Carta de Relacion (1522) by Hernán Cortès, a rare inquisitorial manuscript known as El Abecedario, old printed books, and published collections of linguistic documents.